STUDY AND ANALYSIS OF FACTORS AFFECTING HEALTH (International journal of medical sciences, 2026)
This article examines the major determinants of health, including biological, social, environmental, and lifestyle-related factors. The study analyzes their interrelationship and impact on individual and public health outcomes based on scientific literature. Furthermore, the role of the healthcare system and preventive strategies in strengthening population health is discussed. The findings indicate that health is a multifactorial concept requiring a comprehensive and interdisciplinary approach.